Are the Migrant Worker Empowerment Program's Objectives Effective? - Ferdinand Nababan; Matin Matin; Suryadi Suryadi (Journal of International Conference Proceedings, 2022)
Due to the difficulties of obtaining work in Indonesia and the low level of education, some people have been forced to seek employment overseas. However, a good wage outside of Indonesia does not ensure that when they return to Indonesia, they would be self-sufficient with the money they have earned and will not have to work as migrant workers afterwards. The purpose of this study is to assess BPPPTKI Serang's empowerment program for Indonesian migrant workers. This research employs a qualitative approach as well as an evaluation approach. CIPP was employed as the evaluation model (Contexts, Input, Process and Product). This article focuses solely on the product and impact of this empowerment program, and it does not cover other aspects of CIPP. The study's findings revealed that, while the program's idea was excellent, the results were not. The majority of Indonesian migrant workers who return to work overseas demonstrate this. This, of course, goes against the program's stated goal of producing independent migrant workers once they've worked as migrant workers. In terms of concept, this program still has to be improved upon, particularly in the form of a post-program control procedure to encourage migrant workers to be more productive.Â Keywords: migrant workers, CIPP, empowerment program, productive.